Efek Dari Makro, Industri dan Karakter Spesifik Perusahaan Terhadap Non Performing Loan Di Indonesia - Stanley Mulja; Sung Suk Kim (Owner : Riset dan Jurnal Akuntansi, 2023)
The role of the banking sector is very important for the country's economic system, so it is important for banking institutions to maintain their profitability and efficiency. Currently the banking sector is facing the threat of credit risk indicated by the NPL, where this risk can affect the financial well-being and the role of the banking system. This study aims to examine the effect of bank-specific variables, macroeconomic variables, and industry-specific variables on credit risk as indicated by the NPL level in the Indonesian banking sector. The sample used in this study was 46 banks which were companies listed on the Indonesia Stock Exchange (IDX) during the period 2000 to 2020. The results showed that only bank-specific variables, namely bank capitalization, bank performance, loan growth, and bank diversification, were affect the level of NPL banking sector in Indonesia. Meanwhile other bank specific variables, namely bank size, bank inefficiency, ownership concentration, as well as macroeconomic variables (GDP growth, inflation, public debt, unemployment) and industry specific variables (interbank concentration) do not affect the level of credit risk as indicated by the NPL level of the banking sector in Indonesia.